Estimativas de herdabilidades em populações naturais contínuas e fragmentadas de araucaria angustifolia (bertol.) kuntze - Silva, Erica Cristina Bueno da [UNESP] (2014)
Marker-based methods for estimating the coefficient of heritability in natural populations are important because traditional methods may be impractical or introduce bias via interaction genotype-environmental effects, mating system variation and sampling effects. Thus, the aim of this study is to investigate the genetic control of growth traits in Araucaria angustifolia population continuous and fragmented. The following questions will be addressed: i) There are differences in the levels of heritability between different populations and between generations of the same population? and ii) What levels of heritability for growth traits in natural populations? This study was carried out using two populations of A. angustifolia, one being located in the Reserve Forest Genetics Caçador (RGFC), on the plateau north of the state of Santa Catarina, and other is in a small forest fragment of 5, 4 ha (CENI) located on a farm in the highlands of the state of Paraná, in the basins of Iguaçu. The estimates of heritability were carried out using data of genotypes of regeneration and juveniles of CENI population and juvenile of RGFC population. We used four methods to estimate the relatedness between pairwise individuals and three models for estimating the heritability coefficient, all implemented in the Mark program. The heritability estimates for the combination of all methods of estimation of relatedness and heritability models were not significant different from zero, indicating the inadequacy of the data to the models. There is a tendency for a higher genetic control in the regeneration than juvenile stage. The CENI fragmented population had generally higher heritability than the RGFC natural population, indicating higher potential to respond to natural selection. The main conclusion of this study is ...